Bahasa Inggris - Binar Azwar Anas Harfian; Etty Nurmala Fadillah; Natasya Tanzila (Journal of Biology Learning, 2026)
This study aims to analyze the relationship between digital literacy and ICT self-efficacy in improving students' functional skills at Muhammadiyah Senior High Schools in Palembang City. The main focus of the study includes evaluating the level of development of digital tool use for presentation, evaluation, and information organization, as well as conducting a gender-based comparative analysis of tool knowledge and ICT self-efficacy. Using a quantitative paradigm with a descriptive survey method, data were collected from a randomly selected sample of 200 respondents through a self-administered questionnaire that has been tested for validity and reliability. The findings indicate a significant positive correlation, where students with high ICT self-efficacy scores consistently demonstrate superior performance in critical thinking and problem-solving skills. Although awareness of basic tools such as PowerPoint is adequate, the utilization of advanced applications for information evaluation and data organization is still relatively low. Furthermore, a gender gap was found where male students generally have higher ICT self-efficacy, but interventions through training have been proven to empower female students to exceed the average standard. This study concludes that strengthening digital literacy and technology self-efficacy in an inclusive manner is crucial for students' academic readiness in the digital era.